2017
DOI: 10.1007/s13361-017-1836-3
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Organic Peroxides with Alcohols in Atmospheric Pressure Chemical Ionization—the Pitfalls of Quantifying Triacetone Triperoxide (TATP)

Abstract: Over the last several decades, mass spectrometry has become one of the principle methods for compound identification and quantification. While for analytical purposes, fragments which are not fully characterized in terms of origin and intensity as a function of experimental conditions have been used, understanding the nature of those species is very important. Herein we discuss such issues relative to triacetone triperoxide (TATP) and its frequently observed fragment at m/z 89. This "fragment" has been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, the composition of MEKPO remains an unresolved issue to this day, which requires further study. Colizza et al 35 (2018) claimed that since the MEKPO lacked any true 'standard', stability determinations or quantitative analysis of any specific species was not possible. There are only limited studies on the composition of MEKPO.…”
Section: Conversion Of Mek and H 2 O 2 Yield And Reaction Molementioning
confidence: 99%
See 1 more Smart Citation
“…However, the composition of MEKPO remains an unresolved issue to this day, which requires further study. Colizza et al 35 (2018) claimed that since the MEKPO lacked any true 'standard', stability determinations or quantitative analysis of any specific species was not possible. There are only limited studies on the composition of MEKPO.…”
Section: Conversion Of Mek and H 2 O 2 Yield And Reaction Molementioning
confidence: 99%
“…Black et al 36 (2019) claimed that the MEKPO they prepared was confirmed by liquid chromatography-mass spectrometry (LCMS) analysis to contain the linear dimer, trimer, and tetramer as the major constituents, and also the cyclic trimer as a minor constituent. Colizza et al 35 (2018) claimed that there had been no definitive identification of the cyclic MEKPO species. They also provided possible evidence for the presence of the cyclic trimer.…”
Section: Conversion Of Mek and H 2 O 2 Yield And Reaction Molementioning
confidence: 99%
“…In one of their works Oxley and coworkers considered quantification of organic peroxide explosives based on mass spectral analysis [92]. While for analytical purposes, fragments which are not fully characterized in terms of origin and intensity as a function of experimental conditions have been used, understanding the nature of those species is 186 very important.…”
Section: Detectionmentioning
confidence: 99%
“…8 Due to the thermal vaporization process and energetic plasma caused by corona discharge, various kinds of in-source reactions have been reported and attracted many chemists' attentions. K. Colizza et al 9 explored the formation mechanism of unusual fragments of organic peroxides during APCI process. For instance, they discussed the frequently observed fragment of triacetone triperoxide (TATP) at m/z 89 which was identified as the gas-phase reaction product of TATP with one or two methanol molecules/ions.…”
Section: ■ Introductionmentioning
confidence: 99%